Peningkatan Minat Belajar Siswa dengan Menggunakan Model Pelajaran Two Stay Two Stray pada Pelajaran Tematik - Diana, Asdiana (EL-Hadhary: Jurnal Penelitian Pendidikan Multidisiplin, 2023)
The background of the problem in this study was that during this study the learning activities that dominated the classes emphasized the transfer of knowledge and training and knowledge of thematic learning concepts. The problem formulation of this research is how to increase learning interest using the Two Stay Two Stray learning model and those who do not use the Two Stay Two Stray learning model in thematic lessons. The purpose of this study was to determine the increase in learning interest by using the Two Stay Two Stray learning model, and to find out the difference whether there was an increase in learning interest using the learning model. This type of research is descriptive research using a quantitative approach. The results obtained in this study were that there was an increase in learning interest by using the Two Stay Two Stray lesson model in thematic lessons. Keywords: Improvement, Learning Interest, Two Stay Two Stray Lesson Model, Thematic